Cascade scaffold of porous carbon-coated carbon derivates from a bimetallic zeolitic imidazolate framework for use as an efficient sulfur host in high-performance Li-S batteries. Issue 1 (18th August 2022) - Zheng, Yifan; Feng, Wangjun
Abstract: Currently, there is increasing concern about meeting energy demands, and a lithium-sulfur (Li-S) battery is a promising candidate for use in next-generation energy storage systems. However, some problems still limit the practical implementation of Li-S batteries. Herein, we present a conductive cascade scaffold developed by depositing a porous carbon over a nanoporous carbon layer derived from bimetallic zeolitic imidazolate (BMZIF) as an efficient sulfur host for use in Li-S batteries. Due to the increased conductivity, abundant active sites and large surface area of this prepared material, the assembled Li-S batterie exhibits excellent rate and long cycling performances. Results show an outstanding reversible cycling capacity above 1004.1 mAh/g at 0.2 C for over 100 cycles. This work is designed to effectively address the problems of sulfur electrodes and proposes a new scheme of hosting sulfur in Li-S batteries.